(Safe) Water as the Condition for Sustainable Development in Light of the Climate Crisis: An Eastern Orthodox Reflection - Asproulis, Nikolaos (Religions, 2024)
After reflecting on the issue of (safe) water in the context of SDG 6 with the support of the most recent scientific data, the present study provides clear theological reasoning based on insights developed within the Eastern Orthodox tradition, such as ontological interconnectedness, deep incarnation, and cosmic liturgy towards an eco-ethos which can contribute to sustainable environmental development.